Comparing differences in the spatiotemporal patterns between resident tourists and non-resident tourists using hotel check-in registers. (July 2021) - Xu, Yuquan; Ran, Xiaobin; Liu, Yuewen; Huang, Wei
Abstract: Previous research studied the spatiotemporal patterns in different visitor segments but lacks evidence of the segmentation of resident tourists and non-resident tourists in multi-city travel. To fill this gap, this study conducts a big data study using hotel check-in registers. The exploratory data analysis visualizes the spatiotemporal patterns and the differences between resident tourists and non-resident tourists. Then, the spatiotemporal patterns are measured by the length of stay and the number of visited cities. The regression shows that both the length of stay and the number of visited cities of non-resident tourists are higher than those of resident tourists. Moreover, non-resident tourists reduce their length of stay and their number of visited cities more than resident tourists on three-day holidays, while they increase their number of visited cities less than resident tourists on seven-day holidays. This study has significant implications for understanding spatiotemporal patterns and visitors' segmentations. Highlights: This study uses hotel check-in registers to examine the spatiotemporal patterns of tourists. Resident tourists travel on short holidays, while non-resident tourists travel on long holidays. Resident tourists travel in high GDP cities, while non-resident tourists travel in high tourism revenues cities. The spatiotemporal patterns of non-resident tourists are different from those of resident tourists during public holidays.